Contrasting grazing practices alter plant community trajectories across western Canada’s grasslands with implications for ecosystem function - Timm F. Döbert; Lysandra A. Pyle; Carter Case; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang; Laio Silva Sobrinho; Majid Iravani; Mark S. Boyce (Agriculture, Ecosystems & Environment, 2025)

Using bioinformatics to investigate functional diversity: a case study of MHC diversity in koalas - Luke W. Silver; Elspeth A. McLennan; Julian Beaman; Karen Burke da Silva; Peter Timms; Carolyn J. Hogg; Katherine Belov (Immunogenetics, 2024)
Conservation genomics can greatly improve conservation outcomes of threatened populations, including those impacted by disease. Understanding diversity within immune gene families, including the major histocompatibility complex (MHC) and toll-like receptors (TLR), is important due to the role they play in disease resilience and susceptibility. With recent advancements in sequencing technologies and bioinformatic tools, the cost of generating high-quality sequence data has significantly decreased and made it possible to investigate diversity across entire gene families in large numbers of individuals compared to investigating only a few genes or a few populations previously. Here, we use the koala as a case study for investigating functional diversity across populations. We utilised previous target enrichment data and 438 whole genomes to firstly, determine the level of sequencing depth required to investigate MHC diversity and, secondly, determine the current level of diversity in MHC genes in koala populations. We determined for low complexity, conserved genes such as TLR genes 10 × sequencing depth is sufficient to reliably genotype more than 90% of variants, whereas for complex genes such as the MHC greater than 20 × and preferably 30 × sequencing depth is required. We used whole genome data to identify 270 biallelic SNPs across 24 MHC genes as well as copy number variation (CNV) within class I and class II genes and conduct supertype analysis. Overall, we have provided a bioinformatic workflow for investigating variation in a complex immune gene family from whole genome sequencing data and determined current levels of diversity within koala MHC genes.

Late Cenozoic paleovalley fill sequence from the Southern Liverpool Plains, New South Wales—implications for groundwater resource evaluation - R. I. Acworth; W. A. Timms; B. F. J. Kelly; D. E. Mcgeeney; T. J. Ralph; Z. T. Larkin; G. C. Rau (Australian Journal of Earth Sciences, 2015)

A reassessment of the Lower Namoi Catchment aquifer architecture and hydraulic connectivity with reference to climate drivers - B. F. J. Kelly; W. Timms; T. J. Ralph; B. M. S. Giambastiani; A. Comunian; A. M. McCallum; M. S. Andersen; R. S. Blakers; R. I. Acworth; A. Baker (Australian Journal of Earth Sciences, 2014)

Cellular and molecular basis for endometriosis-associated infertility - Julie A. W. Stilley; Julie A. Birt; Kathy L. Sharpe-Timms (Cell and Tissue Research, 2012)

Evidence for connected water processes through smectite-dominated clays at Breeza, New South Wales - R. I. Acworth; W. A. Timms (Australian Journal of Earth Sciences, 2009)

Optimising subsurface well design for coastal desalination water harvesting - D. J. Anderson; W. A. Timms; W. C. Glamore (Australian Journal of Earth Sciences, 2009)

Western Indian Ocean marine and terrestrial records of climate variability: a review and new concepts on land–ocean interactions since AD 1660 - J. Zinke; M. Pfeiffer; O. Timm; W.-Ch. Dullo; G. J. A. Brummer (International Journal of Earth Sciences, 2009)

Differential Response of Aquatic Oligochaete Species to Increased Nutrient Availability – a Comparative Study between Estonian and Dutch Raised Bogs - G. A. van Duinen; T. Timm; A. J. P. Smolders; A. M. T. Brock; W. C. E. P. Verberk; H. Esselink (Hydrobiologia, 2006)

Propagation of pressure change through thick clay sequences: an example from Liverpool Plains, NSW, Australia - W. A. Timms; R. I. Acworth (Hydrogeology Journal, 2005)

Genetic Variation in Captive Koalas (Phascolarctos cinereus): Parentage Determination and Individual Identification - E. V. Fowler; B. A. Houlden; W. B. Sherwin; P. Hoeben; P. Timms (Biochemical Genetics, 1998)

Influenza A Outbreak among Adolescents in a Ski Hostel - O. Lyytikäinen; E. Hoffmann; H. Timm; B. Schweiger; W. Witte; U. Vieth; A. Ammon; L. R. Petersen (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Influenza a outbreak among adolescents in a ski hostel - O. Lyytikäinen; E. Hoffmann; H. Timm; B. Schweiger; W. Witte; U. Vieth; A. Ammon; L. R. Petersen (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

Erratum - Herman Timm; M. Yamaguchi; M. D. Clegg; J. C. Bishop; Guy W. Bishop; G. C. Upreti; B. B. Nagaich; E. F. Maas; J. P. Sweeney; V. J. Chapman; P. A. Hepner; R. M. Reeve (American Journal of Potato Research, 1968)